Implementation of a performance-based financing scheme in Malawi and resulting externalities on the quality of care of non-incentivized services - Stephan Brenner; Caterina Favaretti; Julia Lohmann; Jobiba Chinkhumba; Adamson S. Muula; Manuela De Allegri (BMC, 2021)
Abstract Background Countries in Africa progressively implement performance-based financing schemes to improve the quality of care provided by maternal, newborn and child health services. Beyond its direct effects on service provision, evidence suggests that performance-based financing can also generate positive externalities on service utilization, such as increased use of those services that reached higher quality standards after effective scheme implementation. Little, however, is known about externalities generated within non-incentivized health services, such as positive or negative effects on the quality of services within the continuum of maternal care. Methods We explored whether a performance-based financing scheme in Malawi designed to improve the quality of childbirth service provision resulted positive or negative externalities on the quality of non-targeted antenatal care provision. This non-randomized controlled pre-post-test study followed the phased enrolment of facilities into a performance-based financing scheme across four districts over a two-year period. Effects of the scheme were assessed by various composite scores measuring facilities' readiness to provide quality antenatal care, as well as the quality of screening, prevention, and education processes offered during observed antenatal care consultations. Results Our study did not identify any statistically significant effects on the quality of ANC provision attributable to the implemented performance-based financing scheme. Our findings therefore suggest not only the absence of positive externalities, but also the absence of any negative externalities generated within antenatal care service provision as a result of the scheme implementation in Malawi. Conclusions Prior research has shown that the Malawian performance-based financing scheme was sufficiently effective to improve the quality of incentivized childbirth service provision. Our findings further indicate that scheme implementation did not affect the quality of non-incentivized but clinically related antenatal care services. While no positive externalities could be identified, we also did not observe any negative externalities attributable to the scheme's implementation. While performance-based incentives might be successful in improving targeted health care processes, they have limited potential in producing externalities - neither positive nor negative - on the provision quality of related non-incentivized services.